Penyuluhan Literasi Keuangan Masyarakat Petani di Desa Tabadamai Kecamatan Jailolo Selatan - Nurdin I Muhammad; Musdar Muhammad; Muhammad Zais M. Samiun (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
The purpose of this service activity is to provide counseling related to the importance of financial literacy to farming communities in Tabadamai village, South Jailolo District; The method of devotion is; using FDG method: Lecture, Practice and Participant Mentoring. To design financial planning, the resource person conveyed that wants and needs must be separated, and can use empty land in the yard of the house, plant kitchen needs in the form of rica, tomatoes and vegetables, so that the distribution of consumption needs can be suppressed, this can add to the increase in seving.savings for the long term, in the form of children's education, ordinary illness and old age.